Islamic Sustainability Education For Accounting Students In Higher Institutions - Muslichah, Muslichah (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2018)
Environmental and social problems are already a global issue. The issue has raised the concept of sustainability and has received great attention from governments, companies, environmentalists, and educational institutions. Many educational institutions have incorporated sustainability education into the curriculum. However, few scientists criticized that the institutions have proven to fail in educating students to make the right decisions. Islamic sustainability education should be an important part of creating a good relationship between people and the environment. All accounting students studying in a higher institution should be equipped with sufficient knowledge to deal with sustainability. Education in higher institutions should not only emphasize the needed skills and knowledge, but it must also instill the religious standards and the commitment of students toward sustainability. The objective of Islamic sustainability education is basically to encourage students to reflect on the kind of sustainability issues that they might encounter so that they will be sensitive to situations that include a sustainability component. If Muslim accounting students are sensitive to sustainability issues, then they are likely to use Islamic moral dimensions in resolving the sustainability problems. Keywords: Islamic sustainability, accounting, education, higher institutions